2018
DOI: 10.1038/s41598-018-23835-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Western diet fed apolipoprotein E-deficient rats exhibit only modest early atherosclerotic characteristics

Abstract: In the apolipoprotein E–deficient mouse, the gut microbiota has an impact on the development of atherosclerosis, but whether such correlations are also present in rats requires investigation. Therefore, we studied female SD-Apoetm1sage (Apoe−/−) rats fed either a Western diet or a low-fat control diet with or without gluten, which is known to promote gut microbiota changes, until 20 weeks of age. We hypothesized that the manifestation of atherosclerosis would be more severe in Apoe−/− rats fed the Western high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…It is unclear why feeding high-fat-diets to ApoE-/-rats stimulated HDL-c. Supplementation of MV stimulated the increase of HDL-c concentrations in the portal vein of ApoE-/-rats fed high-fat diets. Similar results were reported with ApoE-/-rats on high-cholesterol or Western diets [26,27]. However, it could be because the high-fat diets have an impact on the gut microbiota, which in turn changes the lipid profile via bile acid metabolism [14,27].…”
Section: Effects Of Monovalerin On Lipid Metabolismsupporting
confidence: 74%
“…It is unclear why feeding high-fat-diets to ApoE-/-rats stimulated HDL-c. Supplementation of MV stimulated the increase of HDL-c concentrations in the portal vein of ApoE-/-rats fed high-fat diets. Similar results were reported with ApoE-/-rats on high-cholesterol or Western diets [26,27]. However, it could be because the high-fat diets have an impact on the gut microbiota, which in turn changes the lipid profile via bile acid metabolism [14,27].…”
Section: Effects Of Monovalerin On Lipid Metabolismsupporting
confidence: 74%
“…The titre of the applied FVT virome was approximately 2×10 10 virus-like particles/mL (online supplementary figure S1). The mice were subjected to an oral glucose tolerance test (OGTT)20 at week 12 of the study, and food intake and mouse weight were monitored. The study was approved by the Danish Competent Authority, The Animal Experimentation Inspectorate, under the Ministry of Environment and Food of Denmark, and with license ID 2017-15-0201-01262 C1.…”
Section: Methodsmentioning
confidence: 99%
“…#D 98,121,701, Brogaarden Korn & Foder ApS, Lynge, Denmark). Sprague Dawley rats were included as a genetic background control 22 and fed the standard diet (weight, 373.9 ± 7.69, n = 8). All animals had ad libitum access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…With the development of genome editing technology, ApoE KO rats are now available and several studies have showed that atherosclerotic lesions develop slower in rats than in mice 20 , 21 . There is an ongoing discussion about the amount of lesion development in ApoE KO rats, and it appears that the location of targeted genomic change might influence the development of lesions 22 , 23 . To date, there are no comprehensive reports that characterise the vascular properties of ApoE KO rats.…”
Section: Introductionmentioning
confidence: 99%